Social Studies in Al-Qurâan Perspective - Khoiruddin, Muhammad (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2018)
Al-Qurâan perspective on education social support sosio-humanis teosentris paradigm, this by description al-Quran the relationship between human with god (habl min allÃ¢h ) and human and human ( habl maâa al-n Ã¢s ), which are generally suggested that there are two things to be implemented in practice islamic education, the dimensions dialectics horizontally and dimension submission vertical. In dimension dialectics horizontal, educational social life based should be able to develop reality life, both involving with him, the community, and the universe and all its contents, while in dimension submission vertical suggested that education based in social life as a tool to maintain, use and preserve natural resources, also should become a bridge to understand phenomena and honeybee to achieve a perennial with the inventors